PENGARUH KUALITAS PELAYANAN DAN PROMOSI TERHADAP KEPUASAN PELANGGAN PADA ALFAMART DI KABUPATEN SEMARANG - Fia Rafiana; Myra Andriana; Tantik Sumarlin (LPPM Sekolah Tinggi Ilmu Ekonomi - Studi Ekonomi Modern, 2025)
This research aims to identify the impact of service quality and promotion on customer satisfaction at Alfamart in Semarang Regency. The research entity group includes residents in the West Ungaran area of Semarang Regency. The participant selection method uses a non-probability approach, specifically a directed selective method. Participants include West Ungaran residents who have passed the age threshold of 17 years and have previously conducted transactions at Alfamart in Semarang Regency. The information collection mechanism is carried out through the distribution of survey instruments using a multi-level assessment scale. Data is processed through multiple regression testing. The investigative findings reveal that service quality exerts a significant influence on customer satisfaction, based on statistical test results demonstrating the significance value of service quality at 0.000, which falls below 0.05 (0.000 < 0.05), with a test statistic of 5.727 surpassing the critical threshold of 1.986 (5.727 > 1.986). Promotional efforts similarly contribute meaningfully to customer satisfaction, reflected through testing that generated a significance value of 0.002 beneath the 0.05 threshold (0.002 < 0.05) and a test statistic of 3.211 exceeding the critical limit of 1.986 (3.211 > 1.986). Subsequently, customer satisfaction is simultaneously influenced by service quality and promotional strategies, evident from the analysis with a significance value of 0.000 < 0.05 in the simultaneous test and a statistic of 153.608 transcending the critical value of 3.09 in Semarang Regency at Alfamart.